New Directions for the Treatment of Adrenal Insufficiency - Ruiz-Babot, Gerard; Hadjidemetriou, Irene; King, Peter James; Guasti, Leonardo (Frontiers in Endocrinology, 2015)
Adrenal disease, whether primary, caused by defects in the hypothalamic-pituitary-adrenal (HPA) axis, or secondary, caused by defects outside the HPA axis, usually results in adrenal insufficiency, which requires lifelong daily replacement of corticosteroids. However this kind of therapy is far from ideal as physiological demand for steroids varies considerably throughout the day and increases during periods of stress. The development of alternative curative strategies is therefore needed. In this review we describe the latest technologies aimed at either isolating or generating de novo cells that could be used for novel, regenerative medicine application in the adrenocortical field.